Corrosion prevention of magnesium alloys - Song, Guang-Ling (Woodhead Publishing, 2013)
Magnesium is an attractive lightweight metal for many applications. There has therefore been significant research into tackling its major drawback: magnesium's susceptibility to corrosion. This important book summarises key aspects of this research